Total pancreatectomy for diffuse pancreatic adenocarcinoma - Azlanudin A,; Razman J, (Department of Surgery, UKM Medical Centre, 2011)
A 64-year-old lady presented with a brief history of abdominal pain associated with obstructive jaundice. Endoscopic retrograde cholangiopancreaticography (ERCP) revealed a short segment stricture with contact bleeding and the brush cytology confirmed presence atypical cells. Ca 19.9 levels were markedly elevated. She was planned for a Whipple’s procedure but was instead subjected to a total pancreatectomy based on intraoperative findings of a diffusely hard and nodular pancreas. Histopathological examination confirmed our diagnosis of diffuse pancreatic adenocarcinoma. This rare presentation of a locally contained and fully resectable diffuse pancreatic adenocarcinoma is being discussed.